A reference guide for the Business Outlook Survey - David Amirault; Naveen Rai; Laurent Martin (Bank of Canada, 2020)
In 1997, the Bank of Canada established regional offices to enhance communication and liaison activities across the country and to gather more effective regional input for the Bank's policy deliberations. Shortly thereafter, the regional offices began conducting the Business Outlook Survey (BOS)-a quarterly face-to-face survey of senior managers at Canadian firms. The BOS has become an important part of monetary policy deliberations at the Bank of Canada and is also well known in Canadian policy and financial circles. This paper compiles more than 20 years of experience conducting the BOS and serves as a comprehensive reference manual. More specifically, it provides a brief history of the BOS; explains and discusses the survey's sampling strategy and other elements of its design and implementation; highlights some demographic characteristics of the firms that participate; assembles a list of special topics addressed in both the quarterly BOS and the ad-hoc surveys conducted by regional offices; discusses some BOS questions not regularly published; and updates and augments an earlier assessment (Martin and Papile 2004) of the information content of BOS indicators.
Keywords: C83; D22; E32; 330; Firm dynamics; Regional economic developments